РУССКИЙ НАЦИОНАЛЬНЫЙ ХАРАКТЕР В ОЦЕНКЕ ЧЕСЛАВА МИЛОША - Popiel-Machnicki, Wawrzyniec (Acta Neophilologica, 2014)
The assessment of our eastern neighbour made by Czesław Miłosz seems to be very interesting especially in the context of current events in Russia and Ukraine as well as mass media comments on the attempts at the recreation of the Russian empire. Our Nobel Prize winner knew Russia and Russian people very well. He was an expert at Russian literature and wrote numerous essays about this country. Miłosz as an advocate of “a little homeland” was concerned about Russian imperial attitudes. He took it into consideration while evaluating the achievements of Russian writers, thinkers and Nobel laureates in literature. It was also the reason for a heated dispute with Joseph Brodsky.